Determining the value contribution of emicizumab (Hemlibra®) for the prophylaxis of haemophilia A with inhibitors in Spain by multi-criteria decision analysis. (October 2019) - Álvarez-Román, Maria Teresa; Cuervo-Arango, Ignacio; Pérez-Santamarina, Rafael; Poveda, José Luís; Romero, José Antonio; Santamaría, Amparo; Trillo-Mata, José Luís; Tort, Marina; Badia, Xavier
Patients with moderate to severe haemophilia A are at a higher risk of developing FVIII inhibitors that require the use of more costly and less effective treatments. The objective of this study was to determine the value of emicizumab for the prophylaxis of haemophilia A with inhibitors compared to the current therapeutic alternatives, activated prothrombin complex concentrate and recombinant factor VIIa through reflective Multi-Criteria Decision Analysis. The EVIDEM framework adapted to orphan drugs and weighted by a sample of 98 national and regional Spanish evaluators was used. Two structured evidence matrices were developed: emicizumab against activated prothrombin complex concentrate and emicizumab against recombinant factor VIIa. A multidisciplinary team of haemophilia experts rated each of the criteria. Mean and standard deviation were calculated by each criterion and discussed among all participants. Haemophilia A with inhibitors was perceived as a severe disease with high unmet needs. Emicizumab was rated with higher efficacy, therapeutic benefit and quality of life than comparators. When administered alone for the prevention of bleeding events, emicizumab had slightly better safety and tolerability profile than activated prothrombin complex concentrate and similar with recombinant factor VIIa. The inclusion of emicizumab in clinical practice guidelines was valued positively by the members of the panel. Overall, value of emicizumab was higher than activated prothrombin complex concentrate and recombinant factor VIIa, mostly because of efficacy and therapeutic benefit in reducing treated haemorrhages. Reflective Multi-Criteria Decision Analysis has proven to be a feasible method to determine the value contribution of comparative therapies in haemophilia.